La Robe à la Française et la Robe l'Odalisque: Wearing women's clothing in The Rose of Versailles. Issue 1 (1st June 2021) - King, Emerald L.
The androgynous heroine of Ikeda Ryoko's manga The Rose of Versailles (1972‐73), Oscar Françoise de Jarjayes, is usually depicted in masculine, specifically military, attire. The sixth daughter of an important military colonel during the reign of Louis XV and Louis XVI, Oscar is raised as a son and follows her father into the military. Oscar is only ever depicted in one dress, known as the robe l'odalisque ‐ a gown that is adopted at a pivotal moment of character development. It is while wearing this dress, which Ikeda intended to serve as a wedding dress, that Oscar comes to terms with her unrequited love for Marie Antoinette's lover, Count Axel von Fersen. In doing so, Oscar places more importance on her allegiance to France than to romance. This article investigates the complicated gender and social politics that are symbolized by the choice to wear women's clothing in The Rose of Versailles.